2011
DOI: 10.1007/s11670-011-0059-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between hyaluronic acid, hyaluronic acid synthase and human renal clear cell carcinoma

Abstract: Objective: To study the correlation between hyaluronic acid (HA), hyaluronic acid synthase (HAS) and human renal clear cell carcinoma (RCCC).Methods: The expression of three HAS isoforms' gene and HA in 93 RCCC tissues, 27 nephridial tissues by the side of RCCC from two hospitals were measured with Real-Time RT-PCR、Western Blot and immunohistochemical methods and analyzed.Results: All RCCC and adjacent normal tissues expressed three HASs' mRNA & protein; at the mRNA level, both RCCC and adjacent normal tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…There was no difference in expression between normal and tumor tissues among other members of the HA family including HAS2, HAS3, HYAL2, HYAL3, PH20, HYALP1 and CD44v. Cai et al (109) found that the expression of HAS1-3 mRNA in human ccRCC was higher than that in adjacent normal renal samples. However, only the HAS3 protein expression was higher in ccRCC tissues at the protein level.…”
Section: Ha In Rccmentioning
confidence: 99%
“…There was no difference in expression between normal and tumor tissues among other members of the HA family including HAS2, HAS3, HYAL2, HYAL3, PH20, HYALP1 and CD44v. Cai et al (109) found that the expression of HAS1-3 mRNA in human ccRCC was higher than that in adjacent normal renal samples. However, only the HAS3 protein expression was higher in ccRCC tissues at the protein level.…”
Section: Ha In Rccmentioning
confidence: 99%